Development and Validation of a Psychological Resilience Scale for Mothers of Children with ASD: Calibration with Rasch-Andrich Model - Alyami, Ibrahim Q. (Journal of Intellectual Disability - Diagnosis and Treatment, 2023)
Background: The present study aimed to develop and validate a psychological resilience scale for mothers of children with ASD using calibration with the Rasch-Andrich model. Methods: A quantitative approach of national survey research design using an online questionnaire was applied. The cross-sectional study involves a sample of mothers of children with ASD in KSA. Purposive sampling was employed. There were 310 mothers of children with ASD. All of them filled in all questions on the scale. Findings: Concerning unidimensionality and local independence assumptions, the first factor explains more than (20%) of the variance in score with respect to the total variance due to all factors, so it can be said that there is one factor behind the items of the scale. The separation index and reliability of the psychological resilience scale for mothers of children with ASD were at an acceptable level. The person separation reliability was 0.96, indicating an acceptable degree of confidence in replicating the placement of persons within measurement error. Conclusion: Analysis by Item Response Theory (IRT) models allows a considerably deeper understanding of the psychometric properties of the items and scale.